Implementation of Green Materials in Construction Management System in Malaysia - Chong, Jia Hao; Liu, Madelyn Shiu; Hernandes, Erika; Albescu, Mihaela (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
Construction industry plays an important role in social, economic and environmental developments. However, the unstainable development in the industry has led to environmental issues. Construction waste is one of the biggest problems in the construction industry. In Malaysia, construction waste constitutes a large portion of solid waste every year. Most of the construction waste ends up in landfill without proper treatment. The constriction waste can further lead to other environmental issues. In addition, construction activities have also led to environmental issues such as water pollution, air pollution and noise pollution in the country. Besides, utilization of conventional construction materials in the country also leads to unstainable development in the industry. Conventional concrete is the most used construction material and also the most generated construction waste in a construction project. The production of conventional concrete emits a huge amount of carbon dioxide (CO2) (due to the use of cement), which accounts for 8% to 10% of global anthropogenic CO2 emissions every year. Thus, environmental management practices and utilization of green materials can be the keys to achieve sustainable development in the Malaysian construction industry.